2021
DOI: 10.3390/pharmaceutics13020127
|View full text |Cite
|
Sign up to set email alerts
|

Nano Co-Crystal Embedded Stimuli-Responsive Hydrogels: A Potential Approach to Treat HIV/AIDS

Abstract: Currently, the human immunodeficiency virus (HIV) that causes acquired immunodeficiency syndrome (AIDS) can only be treated successfully, using combination antiretroviral (ARV) therapy. Lamivudine (3TC) and zidovudine (AZT), two compounds used for the treatment of HIV and prevention of disease progression to AIDS are used in such combinations. Successful therapy with 3TC and AZT requires frequent dosing that may lead to reduced adherence, resistance and consequently treatment failure. Improved toxicity profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…This has been demonstrated in the manufacture of an NCC formulation to potentially delivery both lamivudine and zidovudine for the management of HIV/AIDS. 48,55,81,82…”
Section: Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been demonstrated in the manufacture of an NCC formulation to potentially delivery both lamivudine and zidovudine for the management of HIV/AIDS. 48,55,81,82…”
Section: Opportunitiesmentioning
confidence: 99%
“…This has been demonstrated in the manufacture of an NCC formulation to potentially delivery both lamivudine and zidovudine for the management of HIV/AIDS. 48,55,81,82 Similarly, Pi et al, demonstrated the possibility of combining the botanical therapeutic baicalein and nicotinamide to improve the solubility of the baicalein. 41 The authors were able to manufacture a formulation capable of increasing the bioavailability of the baicalein while also being able to deliver nicotinamide.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Implants can also be made as stimuli-responsive delivery systems, but the currently marketed implants extended the release but do not change the rate of the drug release. There are many ongoing studies related to stimuli-responsive polymeric implants [37,[69][70][71]. Felipe et al prepared an implant for the delivery of bimatoprost for treatment of glaucoma and ocular hypertension; in a 12-week study, they showed that a bimatoprost implant was not inferior to timolol and it has potential for improved adherence and decrease the treatment of glaucoma [72].…”
Section: Intraocular Implantsmentioning
confidence: 99%
“…In general the inclusion of polymers, lipids, and surfactants for the production of suitable carriers for medicinal and non-medicinal applications has been demonstrated and opportunities to produce technologies that exhibit advantages over conventional formulations including improved stability, enhanced and beneficial biodistribution profiles, altered drug release rates, lower immunotoxicity and with potential targeting of specific cells, exists [ 108 ]. Micro- and/or nano-encapsulation has been used to develop sustained/prolonged drug delivery technologies [ 30 , 109 , 110 ], minimise degradation in biological fluids [ 111 ], facilitate handling [ 112 ] reduce toxicity [ 109 , 113 , 114 , 115 ] and to improve the organoleptic properties [ 19 , 116 , 117 ] of products.…”
Section: Encapsulation and Evaluation Of Therapeutic Benefits Of Curmentioning
confidence: 99%